Effect of fertilisation with urea on development in the ornamental bromeliad Aechmea fasciata - Patricia Giampaoli (Revista Ciência Agronômica, 2017)
The aim of this study was to evaluate the effect of urea fertiliser on the bromeliad, Aechmea fasciata . Plants were submitted to weekly treatments with a solution of 0.0, 0.5, 1.0, 1.5 or 2.0 g urea L -1 . After 210 days of the experiment, biometric variables of growth and development of the root and shoot systems were analysed, together with foliar levels of chlorophyll a and b , and of carotenoids. The experimental design was of randomised blocks with four replications; eight plants were used per plot. The data were submitted to regression analysis. The highest values for chlorophyll a and carotenoid content were obtained at a concentration of 1.23 g L -1 urea, and for chlorophyll b at a concentration 1.75 g L -1 urea. Plants of A. fasciata submitted to a solution with no nitrogen showed marked chlorosis of the leaves and reduced growth and development. The mean value for the maximum levels of photosynthetic pigments was 1.40 g L -1 urea, and this can be used as an indicator of the nutritional status of nitrogen in the species. From the results, an application of 1.46 g L -1 urea to the tank in A. fasciata is recommended, as this gave the greatest accumulation of total dry weight and an increase in the number of leaves.